Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae) - Fanciulli, Pietro Paolo; Leo, Chiara; Convey, Peter; Frati, Francesco; Carapelli, Antonio (Zootaxa, 2018)
Fanciulli, Pietro Paolo, Leo, Chiara, Convey, Peter, Frati, Francesco, Carapelli, Antonio (2018): Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae). Zootaxa 4392 (2): 392-400, DOI:10.11646/zootaxa.4392.2.11